Conventional and advanced food processing technologies / Suvendu Bhattacharya - Bhattacharya, Suvenduedited by
"This book will discuss conventional and advanced food processing techniques in detail, outlining their specific applications along with examples, models, and suggestions for further reading for students and professionals, including those without an advanced background knowledge of food processing. Section1 will be dedicated to the conventional food processing techniques which are presently the most widely used